You Think of Ev'rything - Jimmy Van Heusen::::::::: (Robbins Music Corporation)
Piano and vocal score, 5 p. Featured in Billy Roses New Aquacade at the New York Worlds Fair 1940. At head of title on cover: Popular edition, On cover: Featured in Billy Roses New Aquacade at the New York Worlds Fair 1940, Staged by John Murray Anderson scenery and costumes by Raoul Pene Du Bois, Port. of Eleanor Holm on cover. Publishers advertisements on p.[2] and verso of last leaf.